UJI BAKTERI Escherichia coli PADA MINUMAN SUSU KEDELAI DARI BEBERAPA PENJUAL SUSU KEDELAI DI KOTA SURAKARTA - Murtiningtyas, Sandy (2016)
Soybean is one of food materials that has many benefits. One of soybean products is soybean milk drink. Nevertheless, if the process of its making is not good, it can be contaminated with bacteria coliform, one of the bacterias is bacteria Escherichia coli. Bacteria Escherichia coli that enters the body can cause symptoms like diarhea and gastroenteritis. Bacteria Escherichia coli can be used as an indicator of contamination in water or drink by bacteria derived from feces. The bacteria can spread through many ways such as through water or contaminated foods. This research aimed at knowing the description of the quality of soybean milk drink and knowing the amount of bacteria Escherichia coli in the soybean milk drinks sold by several sellers in Surakarta city. This research used sample as many as ten samples. After that, an examination was conducted on the samples to know the existence of bacteria Escherichia coli through three steps, they were: test of estimation, test of confirmation, and complete test. Population of bacteria Escherichia coli in each sample was calculated using the method of Most Probable Number (MPN). From the results of the research, it was obtained data that the ten samples tested had a negative score on bacteria Escherichia coli. The conclusion of this research was that bacteria Escherichia coli was not found in the samples of soybean milk drinks from several soybean milk sellers in Surakarta city, therefore, the drink had been appropriate to the Indonesian National Standard (SNI).